Neurotrauma and Inflammation: CNS and PNS Responses - Bruno Siqueira Mietto; Klauss Mostacada; Ana Maria Blanco Martinez (Mediators of Inflammation, 2015)
Traumatic injury to the central nervous system (CNS) or the peripheral nervous system (PNS) triggers a cascade of events which culminate in a robust inflammatory reaction. The role played by inflammation in the course of degeneration and regeneration is not completely elucidated. While, in peripheral nerves, the inflammatory response is assumed to be essential for normal progression of Wallerian degeneration and regeneration, CNS trauma inflammation is often associated with poor recovery. In this review, we discuss key mechanisms that trigger the inflammatory reaction after nervous system trauma, emphasizing how inflammations in both CNS and PNS differ from each other, in terms of magnitude, cell types involved, and effector molecules. Knowledge of the precise mechanisms that elicit and maintain inflammation after CNS and PNS tissue trauma and their effect on axon degeneration and regeneration is crucial for the identification of possible pharmacological drugs that can positively affect the tissue regenerative capacity.